Knowledge Sharing as a Mediator of Leadership and Organizational Communication Toward Innovation - Kiki Kahfi Abdul Fatah; Nidya Dudija (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The electricity industry faces increasing demands for continuous innovation amid rapid technological advancement and rising customer expectations. Innovative capability is assumed to be influenced not only by leadership and organizational communication but also by the effectiveness of knowledge sharing in facilitating the flow and utilization of organizational knowledge. This study examines the effects of leadership and organizational communication on innovation by incorporating knowledge sharing as a mediating variable. Using a quantitative approach with employee survey data and Partial Least Squares–Structural Equation Modeling (PLS-SEM), the study evaluates the structural relationships and both direct and indirect effects. The findings indicate that leadership has a significant positive effect on knowledge sharing, and organizational communication also positively influences knowledge sharing. Knowledge sharing significantly enhances innovation, while the direct effects of leadership and communication on innovation are not significant. Mediation analysis confirms that knowledge sharing significantly mediates both the leadership–innovation and communication–innovation relationships. These findings highlight that innovation increases primarily when leadership and communication practices are reinforced through structured knowledge-sharing mechanisms.